Internet connectivity disruption in Bolivia (Bolivia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Bolivia. Data sourced from IODA.
Network Disruption Incident ID: BO-2026-0016. Severity: critical. Confidence: 65%